Connecting Tutors and Students: A Mobile Application Designed with Design Thinking - Mambu, Joe Yuan; Lakat, Junior; Tangka, George Morris William (CogITo Smart Journal, 2024)
The rapid advancement of information technology has transformed education globally, but in regions like Manado, Indonesia, the lack of platforms connecting private tutors with students creates inefficiencies. Students face difficulties in finding affordable tutoring services, while tutors struggle with marketing and building trust. This study aims to design and evaluate the user interface (UI) and user experience (UX) of a mobile application addressing these challenges using the Design Thinking methodology. Through five stages—Empathize, Define, Ideate, Prototype, and Test—key pain points were identified, including scheduling inefficiencies, trust issues, and geographical constraints. Solutions like flexible scheduling, integrated promotional tools, and rating systems were proposed. Prototypes, developed using Figma, were tested through usability evaluations across four scenarios. Key findings include: Scenario 3 (notifying a tutor) showed optimal performance with a task completion time of 2 seconds, no miss-clicks, and a usability score of 100; Scenario 1 (finding courses via maps) had a 95 usability score with an 8% miss-click rate; Scenario 2 (finding schedules) showed a 25% miss-click rate and a usability score of 80; and Scenario 4 (checking notifications) faced significant challenges, with a 50% miss-click rate and a usability score of 75. These results underscore the effectiveness of Design Thinking in addressing the needs of users and provide valuable insights for improving educational platforms in underserved regions. The findings suggest that while the mobile app holds great potential for improving educational access, further refinements are needed, particularly in navigation and notification features.